2014
DOI: 10.1038/ncomms6338
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of the phytosphingosine metabolic pathway leading to odd-numbered fatty acids

Abstract: The long-chain base phytosphingosine is a component of sphingolipids and exists in yeast, plants and some mammalian tissues. Phytosphingosine is unique in that it possesses an additional hydroxyl group compared with other long-chain bases. However, its metabolism is unknown. Here we show that phytosphingosine is metabolized to odd-numbered fatty acids and is incorporated into glycerophospholipids both in yeast and mammalian cells. Disruption of the yeast gene encoding long-chain base 1-phosphate lyase, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 44 publications
4
81
0
Order By: Relevance
“…Although the anterior half of the PHS degradation pathway is similar to those of DHS and SPH (Figs. S1 and S2), the latter half is completely different and largely unknown but includes an FA α-oxidation step (27). We identified MPO1 as a gene involved in the PHS degradation pathway, likely in the FA α-oxidation step, in yeast (27), whereas an Mpo1 homolog does not exist in mammals.…”
Section: Significancementioning
confidence: 94%
See 4 more Smart Citations
“…Although the anterior half of the PHS degradation pathway is similar to those of DHS and SPH (Figs. S1 and S2), the latter half is completely different and largely unknown but includes an FA α-oxidation step (27). We identified MPO1 as a gene involved in the PHS degradation pathway, likely in the FA α-oxidation step, in yeast (27), whereas an Mpo1 homolog does not exist in mammals.…”
Section: Significancementioning
confidence: 94%
“…Levels of PHS-containing CERs (PHS-CERs) are reduced in atopic dermatitis patients (26), implying the importance of PHS-CERs in epidermal permeability barrier formation. We recently revealed that PHS is metabolized to pentadecanoic acid (C15:0-COOH) via 2-OH C16:0-COOH in yeast and mammals (27). Thus, the PHS degradation pathway is another supply source of 2-OH FAs, in addition to FA2H.…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations